2020
DOI: 10.1038/s41598-020-68562-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mandibular body changes in growing subjects: a comparison of CBCT and reconstructed lateral cephalogram measurements

Abstract: the aim of this study is to compare cone-beam computed tomography (cBct) and bi-dimensional reconstructed lateral cephalograms (RLcs) in assessing mandibular body length and growth and to evaluate how mandibular reshaping influences the error in measuring mandibular body growth in bi-dimensional radiographs. Twenty-five patients with two CBCT scans taken at a mean distance of 2.21 ± 0.5 years were selected. The following measurements were performed: right and left mandibular body length at each point in time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…TMJ pain could have a negative effect on the normal activities and quality of life in patients with RA [45,46]. These findings were similar to those of previous studies, in which degenerative bone changes were observed on radiographic or magnetic resonance imaging, in patients with TMJ and RA (MRI) [47][48][49]. Meanwhile, Uchiyama et al demonstrated that the incidence of bony deformation in the mandibular condyle was not related to the duration of RA or changes in the other joints [50].…”
Section: Discussionsupporting
confidence: 83%
“…TMJ pain could have a negative effect on the normal activities and quality of life in patients with RA [45,46]. These findings were similar to those of previous studies, in which degenerative bone changes were observed on radiographic or magnetic resonance imaging, in patients with TMJ and RA (MRI) [47][48][49]. Meanwhile, Uchiyama et al demonstrated that the incidence of bony deformation in the mandibular condyle was not related to the duration of RA or changes in the other joints [50].…”
Section: Discussionsupporting
confidence: 83%
“…It should be emphasized, however, that CBCT examination allowed the precise analysis of condylar morphology, but it did not enable the diagnosis of soft tissue inflammation. The abnormalities visible in the radiological examinations result from irregularities within the bone tissue and indicate the chronic nature of the disease [ 26 , 27 ]. The gold standard in TMJ diagnostics in JIA patients is MRI, with which it is possible to visualize not only chronic deformations resulting from a long-term degenerative process but also active inflammation of TMJ, i.e., synovitis [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMJ arthritis may cause damage to articular structures in addition to affecting the mandibular growth center, located below the thin cartilage layer of the articular head of the condylar process, thus contributing to the inhibition of mandibular growth [ 4 , 27 ]. The growth center is responsible for the growth of the entire mandible (body, ramus, and angle).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations